Aurachins, Bacterial Antibiotics Interfering with Electron Transport Processes - Sebastian Kruth; Markus Nett (MDPI AG, 2023)
Aurachins are farnesylated quinolone alkaloids of bacterial origin and excellent inhibitors of the respiratory chain in pro- and eukaryotes. Therefore, they have become important tool compounds for the investigation of electron transport processes and they also serve as lead structures for the development of antibacterial and antiprotozoal drugs. Especially aurachin D proved to be a valuable starting point for structure-activity relationship studies. Aurachin D is a selective inhibitor of the cytochrome bd oxidase, which has received increasing attention as a target for the treatment of infectious diseases caused by mycobacteria. Moreover, aurachin D possesses remarkable activities against Leishmania donovani, the causative agent of leishmaniasis. Aurachins are naturally produced by myxobacteria of the genus Stigmatella as well as by some Streptomyces and Rhodococcus strains. The recombinant production of these antibiotics turned out to be challenging due to their complex biosynthesis and their inherent toxicity. Recently, the biotechnological production of aurachin D was established in E. coli with a titer which is higher than previously reported from natural producer organisms.